Interferon-λ Improves the Efficacy of Intranasally or Rectally Administered Influenza Subunit Vaccines by a Thymic Stromal Lymphopoietin-Dependent Mechanism - Ye, Liang; Schnepf, Daniel; Ohnemus, Annette; Ong, Li Ching; Gad, Hans Henrik; Hartmann, Rune; Lycke, Nils; Staeheli, Peter (Frontiers in Immunology, 2021)
Previous work showed that interferon-λ (IFN-λ) can trigger the synthesis of thymic stromal lymphopoietin (TSLP) by specialized epithelial cells in the upper airways of mice, thereby improving the performance of intranasally administered influenza vaccines. Here we demonstrate that protein-only influenza vaccines containing either IFN-λ or TSLP boosted antigen-specific IgG1 and IgA responses and enhanced the resistance of mice to influenza virus challenge, irrespective of whether the vaccines were applied via the intranasal or the rectal route. TSLP receptor deficiency negatively influenced vaccine-induced antiviral immunity by impairing the migration of dendritic cells from the airways to the draining lymph nodes of immunized mice, thereby restraining follicular helper T cell and germinal center B cell responses. As previously observed during intranasal vaccination, the adjuvant effect of IFN-λ on a rectally administered influenza vaccine was no longer observed when TSLP receptor-deficient mice were used for immunization, highlighting the central role of the IFN-λ/TSLP axis for vaccine-induced antiviral immunity in the mucosa.